Weighted Estimates for Commutators of n-Dimensional Rough Hardy Operators - Zhuanxi Ren; Shuangping Tao (Journal of Function Spaces and Applications)
We establish the weighted estimates for the commutators HΩ,b and HΩ,b∗ which are generated by the n-dimensional rough Hardy operators and central BMO functions on the weighted Lebesgue spaces, the weighted Herz spaces and the weighted Morrey-Herz spaces. Furthermore, the weighted Lipschitz estimates are also obtained.